Penilaian Kinerja Keuangan Pemerintah Daerah Kota Bogor Periode Tahun 2012 - 2016 - Isnurrini Hidayat Susilowati; Julia Retnowulan; Wiwik Widiyanti (Widya Cipta - Jurnal Sekretari dan Manajemen, 2018)
One of the form of authorities that has been given by the goverment in order to fulfill the autonomous region for managing the areais the financial aspect. The purpose of the performance measurement of the goverment is to improve the goverment’s performance itself, allocate the resources that we have, and make some decisions to realize public accountabilities. The form of performance measurements for the goverment is done by conducting a financial analysis of The regional Expenditure Budget (APBD) that has been established and implemented before. The type of research that has been conducted by the researcher is quantitative descriptive. The result of studi indicate financial perfoemance of the city goverment of Bogor is good. It means that the average amount of PAD Bogor from 2012- 2016 is 26,96 % which is compared with the total regional incomes.The effectiveness of Bogor’s regional financial management could happen because it uses an effetive relationship pattern on average above 100%. The ratio of direct expenditure to total expenditure in Bogor from2012 – 2014 experienced the highest increase, the highest ratio is happened in 2014 54,21%. The PAD growth ratio shows a positive result despite of showing a sharp decline in 2016 of 8,61%.